Tobacco carcinogen 4-[methyl(nitroso)amino]-1-(3-pyridinyl)-1-butanone (NNK) drives metabolic rewiring and epigenetic reprograming in A/J mice lung cancer model and prevention with diallyl sulphide (DAS). (9th December 2021) - Hudlikar, Rasika R; Sargsyan, Davit; Cheng, David; Kuo, Hsiao-Chen Dina; Wu, Renyi; Su, Xiaoyang; Kong, Ah-Ng
Abstract: Early detection of biomarkers in lung cancer is one of the best preventive strategies. Although many attempts have been made to understand the early events of lung carcinogenesis including cigarette smoking (CS) induced lung carcinogenesis, the integrative metabolomics and next-generation sequencing approaches are lacking. In this study, we treated the female A/J mice with CS carcinogen 4-[methyl(nitroso)amino]-1-(3-pyridinyl)-1-butanone (NNK) and naturally occurring organosulphur compound, diallyl sulphide (DAS) for 2 and 4 weeks after NNK injection and examined the metabolomic and DNA CpG methylomic and RNA transcriptomic profiles in the lung tissues. NNK drives metabolic changes including mitochondrial tricarboxylic acid (TCA) metabolites and pathways including Nicotine and its derivatives like nicotinamide and nicotinic acid. RNA-seq analysis and Reactome pathway analysis demonstrated metabolism pathways including Phase I and II drug metabolizing enzymes, mitochondrial oxidation and signaling kinase activation pathways modulated in a sequential manner. DNA CpG methyl-seq analyses showed differential global methylation patterns of lung tissues from week 2 versus week 4 in A/J mice including Adenylate Cyclase 6 (ADCY6), Ras-related C3 botulinum toxin substrate 3 (Rac3). Oral DAS treatment partially reversed some of the mitochondrial metabolic pathways, global methylation and transcriptomic changes during this early lung carcinogenesis stage. In summary, our result provides insights into CS carcinogen NNK's effects on driving alterations of metabolomics, epigenomics and transcriptomics and the chemopreventive effect of DAS in early stages of sequential lung carcinogenesis in A/J mouse model. Graphical Abstract: